Strontium-loaded titanium implant with rough surface modulates osseointegration by changing sfrp4 in canonical and noncanonical Wnt signaling pathways. (1st May 2022) - Wang, Xiaoyi; Xin, He; Ning, Xiaona; Zhang, Yubohan; Liu, Fuwei; Zhang, Zhouyang; Jia, Xuelian; Guo, Weiwei; Hong, Yonglong; Sui, Wen
Abstract: A rough morphology and strontium (Sr) can activate the Wnt pathway to regulate bone mesenchymal stem cells (rBMSCs) osteogenic differentiation, but the mechanism remains unclear. We constructed smooth Ti (ST) surfaces, rough Ti (RT) surfaces subjected to hydrofluoric acid etching, strontium-loaded smooth Ti (ST-Sr) surfaces subjected to magnetron sputtering, and rough strontium-loaded Ti (RT-Sr) surfaces. We systematically studied the in vitro osteogenic differentiation of rBMSCs on these four surfaces by alkaline phosphatase measurement, Alizarin Red staining and polymerase chain reaction (PCR). We also investigated whether crosstalk of the canonical and noncanonical Wnt signaling pathways regulated by sfrp4, which is an inhibitor of canonical and noncanonical Wnt, is the underlying mechanism via PCR on rBMSCs in different stages of osteogenic differentiation. We confirmed the effect of sfrp4 through an in vivo sfrp4-siRNA test. The in vitro osteogenic differentiation of rBMSCs decreased in the order RT-Sr, RT, ST-Sr, and ST. Regarding the mechanism, rough morphology and Sr both enhanced the canonical Wnt pathway to promote osseointegration. Additionally, rough morphology can inhibit sfrp4 to activate the noncanonical Wnt pathway, and then, the activated noncanonical Wnt pathway can suppress the canonical Wnt pathway at the early stage of osteogenic differentiation. Sr continuously enhanced sfrp4 to inhibit the canonical Wnt pathway instead of activating the noncanonical Wnt pathway. Interestingly, the effect of rough morphology on sfrp4 changed from inhibition to enhancement, and the enhancing effect of Sr on sfrp4 was gradually attenuated. The results of the in vivo sfrp4-siRNA test showed that osseointegration decreased in the order RT-Sr, RT-Sr-siRNA, and ST. Our results suggest that the lack of sfrp4 could suppress osseointegration, indicating that sfrp4 acts as a crucial regulatory molecule for the canonical and noncanonical Wnt pathways during the response of rBMSCs to rough morphology and Sr.